2016
DOI: 10.5535/arm.2016.40.4.620
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Tongue Pressure and Oral Dysphagia in Stroke Patients

Abstract: ObjectiveTo evaluate the relationships between tongue pressure and different aspects of the oral-phase swallowing function.MethodsWe included 96 stroke patients with dysphagia, ranging in age from 40 to 88 years (mean, 63.7 years). Measurements of tongue pressure were obtained with the Iowa Oral Performance Instrument, a device with established normative data. Three trials of maximum performance were performed for lip closure pressure (LP), anterior hard palate-to-tongue pressure (AP), and posterior hard palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 23 publications
(27 reference statements)
2
46
0
5
Order By: Relevance
“…Previous studies have reported that tongue strength in patients with dysphagia after stroke has a relationship with the oral phase, particularly with regard to bolus formation, mastication, premature bolus loss, tongue to palate contact and oral transit time (Lee et al . , Oh et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that tongue strength in patients with dysphagia after stroke has a relationship with the oral phase, particularly with regard to bolus formation, mastication, premature bolus loss, tongue to palate contact and oral transit time (Lee et al . , Oh et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…, Lee et al . ). In addition, weakening of the suprahyoid muscles directly affects hyolaryngeal movements causing pharyngeal dysphagia, which can lead to pharyngeal residue and aspiration (Logemann et al .…”
Section: Introductionmentioning
confidence: 97%
“…Thus, the decrease in tongue pressure observed in some cases of stroke was basically associated with the presence of dysphagia. Several studies in the literature have related the decrease in tongue pressure to the symptom of dysphagia (10,20,21,22,23,24) . The results of this study indicated that tongue pressure in the subjects affected with stroke could trigger dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Although impairment of this complex central system contributes to a decrease in the swallowing function, the restoration of this process after the stroke may also depend in part on the recovery of neuromuscular morphological factors, such as the strength of the intrinsic and extrinsic musculature of the tongue (9) . Abnormal tongue function may also favor the presence of oral residue, prolonged oral transit time (3) , difficulty in bolus formation, and premature loss of food (10) . There is evidence that the greatest degree of tongue strength impairment occurs in patients with oropharyngeal dysphagia, compared with those with adequate swallowing (6,8,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Healthy swallowing function is critical for airway safety, nutrition, and quality of life, yet aged individuals frequently develop difficulty swallowing, with dysphagia occurring in 15% to 40% of individuals over age 60 years . Tongue weakness, associated with both old age and dysphagia, has been identified as a therapeutic target. Tongue strengthening exercises increase maximum isometric tongue pressures and improve patient‐reported measures of swallowing .…”
Section: Introductionmentioning
confidence: 99%